The Role of Applying the Sustainability Accounting Standard(the Standard of Transferring Resources for Electrical and Electronic Equipment) in Reducing Costs : (Applied Research in the Battery Factory - Babel 2 Factory (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract:The main objective of the research is to demonstrate the application of the sustainability accounting standard (the standard for transferring resources to electrical and electronic equipment) to reduce costs, as this will achieve what the dimensions of sustainability (economic, environmental, social) seek, as well as reducing production costs and improving the quality of the battery through accreditation On the actual need for workers in line with the requirements of sustainability, and many conclusions were reached, the most important of which is that the application of sustainability accounting standards, especially the standard of transferring resources to electrical and electronic equipment, will maintain product safety and help manage hazardous waste (liquid and solid) for the purpose of preserving the environment and reducing costs, and it was reached To many recommendations, the most important of which is that the general industrial companies should adopt the standard of transferring resources to electrical and electronic equipment, for the purpose of reducing costs